THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON BANK PERFORMANCE IN NIGERIA - Ibrahim Yinka Agbeyinka (Gusau Journal of Accounting and Finance)
The objective of the study was to investigate the impact of corporate social responsibility on bank’s performance in Nigeria. The ex-post-facto research design was adopted, and the study focused on selected banks. A yearly panel series data from 2007-2016 were sourced from the banks’ annual reports and Nigerian Exchange Group. The data was subjected to panel regression analysis to estimate the parameters of the model. The findings revealed that CSR have a significant and positive impact on net profit margin, suggesting that firms actively engaged in corporate social responsibility initiatives tend to experience better profitability. The analysis also shows a negative relationship between corporate social responsibility and earnings per share, indicating that corporate social responsibility may contribute to long-term value creation. Firm size emerges as a crucial factor in determining financial performance. Larger firms generally enjoy higher returns on equity and are more efficient in utilizing their assets to generate returns. The study concluded that the dual-edged nature of corporate social responsibility engagement, where the benefits to profitability and long-term value must be balanced against the potential short-term financial drawbacks. The study therefore recommended that firms should strategically integrate corporate social responsibility initiatives with their core business objectives to maximize the positive impact on profitability. firms should carefully evaluate the timing and scale of their corporate social responsibility investments. Firms should focus on streamlining operations to prevent the erosion of net profit margins. This can be achieved by adopting advanced technologies, optimizing supply chains, and reducing unnecessary overhead costs. Banks should establish clear metrics for evaluating the success of their corporate social responsibility programs, regularly review their impact on financial performance, and adjust as needed to maintain a balance between social responsibility and profitability.